Apprenticeship and the Negotiation of Freedom. The Liberated Africans of the Anglo-Portuguese mixed Commission in Luanda (1844-1870) - Coghe, Samüel (Africana Studia, 2020)
This paper examines the history of the Africans liberated from the slave trade by the Mixed Commission in Luanda in the mid-19th century. Upon their freeing, the liberated Africans were apprenticed for several years before being granted complete freedom. The article argues that the conception and the vicissitudes of this civilizing project were intimately linked to experiences with freed slaves elsewhere in the Atlantic World. Furthermore, it shows that due to the continuous existence of slavery, many actors considered the presence of the semi-free liberated Africans in Luanda undesirable. Keywords: Slave Trade; Abolition; African freedmen, Angola, Atlantic history; apprenticeship.